Our clinical experience about prenatal diagnosis and neonatal outcomes of fetal central nervous system anomalies - Ozkan, Zehra Sema; Cilgin, Hasan; Aygun, Hatice Banu; Deveci, Derya; Simsek, Mehmet; Kumru, Selahattin; Yuce, Huseyin (Informa Healthcare, 2011)
Materials and methods. aEuro integral We reviewed the medical records and ultrasound data of 69 cases diagnosed with CNS anomalies from 2007 to 2008. We described the prenatal diagnosis, associated findings, and outcome of these patients. Results. aEuro integral Sixty-nine patients were diagnosed with CNS anomalies. Of these, 31 had ventriculomegaly ++ hydrocephaly, 14 had spina bifida ++ meningomyelosel, 5 had choroid plexus cyst, 5 had Dandy Walker malformation, 3 had sacrocoxigeal teratoma, 2 had encephalosel, 1 had microcephaly, and 1 had Arnold Chiari malformation. Eight amniocentesis, three cord blood sampling, and two fetal reduction procedure were performed. Nine pregnancy termination and 36 delivery were performed. Neurosurgical correction was performed for neonates with spina bifida, hydrocephaly and sacrocoxigeal teratoma. Twenty-one neonates were discharged with cure, 4 neonates with follow-up, 7 neonates with paraplegia, and 13 neonates died. Conclusion. aEuro integral The outcome of fetuses with CNS anomalies was shown to depend mainly on the degree of neural tube defect and the associated anomalies were the most important factors in surviving.
Keywords: Fetal central nervous system anomalies; neural tube defect; prenatal diagnosis; ventriculomegaly; spina bifida